2019
DOI: 10.1108/jiabr-12-2015-0060
|View full text |Cite
|
Sign up to set email alerts
|

The influence of culture on service quality leading to customer satisfaction and moderation role of type of bank

Abstract: Purpose Considering the importance of current Libyan business environment, this paper aims to understand the influence of culture on perceived service quality that leads to customer satisfaction in the Libyan banking industry. In addition, it would be interesting to explore which type of banks, e.g. public or private banks, moderate the relationship between perceived service quality and customer satisfaction. Design/methodology/approach The data were collected from the customers who are receiving services fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 66 publications
0
42
1
3
Order By: Relevance
“…Sivesan (2019) investigated the relationship between the two in the specific context of insurance companies. There have been numerous studies conducted on the service quality and customer satisfaction of banking customers, proving it to be a strong relation (Devesh, 2019;Endara et al, 2019;Li et al, 2021;Pakurár et al, 2019;Razak et al, 2007). Ramanathan et al (2018) compared the customers of leasing contracts in public and private sectors and suggested responsiveness and assurance be the most important dimensions ensuring an indirect relationship with customer satisfaction.…”
Section: Service Quality and Customer Satisfactionmentioning
confidence: 99%
“…Sivesan (2019) investigated the relationship between the two in the specific context of insurance companies. There have been numerous studies conducted on the service quality and customer satisfaction of banking customers, proving it to be a strong relation (Devesh, 2019;Endara et al, 2019;Li et al, 2021;Pakurár et al, 2019;Razak et al, 2007). Ramanathan et al (2018) compared the customers of leasing contracts in public and private sectors and suggested responsiveness and assurance be the most important dimensions ensuring an indirect relationship with customer satisfaction.…”
Section: Service Quality and Customer Satisfactionmentioning
confidence: 99%
“…Customer focus becomes a significant factor for the success of an organization because it is a starting point of any quality initiative, it is recommended to conduct research in the context of service industries and to specify the long term impact of customer focus towards other organizational performance (Sousa, 2007;Cai, 2009). In measuring customer satisfaction, service quality is the most important thing which is the key for the organizational survival (Endara et al, 2019). Customer focus is one of four TQM elements that has a significant contribution to both the financial and operational performance (Abusa and Gibson, 2011).…”
Section: Customer Focusmentioning
confidence: 99%
“…Contemporary researchers still believe that SERVQUAL and modified SERVQUAL dimensions influence customer satisfaction in medical care organisations (Park et al, 2016). Many authors have conducted studies on the relationship between service quality and customer satisfaction in different contexts and in different industries (Endara et al, 2019;De Bruin et al, 2020). Aljumah et al, (2020) found that service quality affects customer satisfaction among foreigners in Malaysian medical tourism.…”
Section: The Relationship Between Service Quality and Customer Satisfactionmentioning
confidence: 99%
“…Aljumah et al, (2020) found that service quality affects customer satisfaction among foreigners in Malaysian medical tourism. Endara et al's, (2019) Based on debates and discussions in the literature above, this study proposes the following hypothesis: H1: Service quality has a positive impact on customer satisfaction in medical care in the Maldives…”
Section: The Relationship Between Service Quality and Customer Satisfactionmentioning
confidence: 99%